The Significance of the Ki-67 Labeling Index, the Expression of c-kit, p53, and bcl-2, and the Apoptotic Count on the Prognosis of Gastrointestinal Stromal Tumor - Aoyagi, Keishiro; Kouhuji, Kikuo; Shirouzu, Kazuo (IntechOpen, 2012)
None